A novel surface modification method for anhydrite whisker. (5th October 2016) - Hong, Tianzeng; Lv, Zhihui; Liu, Xin; Li, Wu; Nai, Xueying; Dong, Yaping
Abstract: Calcium sulfate anhydrite whisker (CSAW, anhydrous-insoluble) was modified with inorganic-organic surface modification method. The modified-CSAW (M-CSAW) was investigated by field emission scanning electron microscope (FESEM), X-ray powder diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TG). The results indicate that trisodium phosphate and stearic acid have remarkable effects on CSAW. The contact angle of M-CSAW reaches up to 108.43°. Trisodium phosphate actives the surface of CSAW compared to traditional methods (acid or base activation approaches), and then chemical reaction occurs on the surface of CSAW between COO – and Ca 2 + . The M-CSAW can be potentially applied to whisker/polymer composite materials. Graphical abstract: Anhydrite whisker's applications have been limited for a long time due to its poor compatibility with organic matrix in composite area. Surface modification is utilized as an efficient way to solve this problem. In our study, anhydrite whisker was modified via a novel simple method. First, trisodium phosphate was selected to active the surface of anhydrite whisker rather than traditional strong acid or strong base, and then stearic acid grafted on the surface of anhydrite whisker. The modified anhydrite whisker exhibits remarkable hydrophobic property. The resulting of M-CSAW was studied by SEM, FT-IR, XPS and TG to reveal the preparation mechanism. Highlights: Trisodium phosphate was used to active anhydrite whisker surface for the first time. Stearic acid was applied to modify the activated anhydrite whisker surface. Modified anhydrite whisker has remarkable hydrophobic and thermal abilities.